Use of Alginates as Food Packaging Materials - Michael G. Kontominas (Foods, 2020)
Packaging mainly functions by protecting and preserving its contents. In the case of food packaging, the package protects the contained food product from (i) physical/mechanical damage; (ii) physico-chemical changes due to the effect of light, oxygen, moisture and odors; and (iii) biological changes due to the presence of microorganisms and pests; all the above parameters result in the reduction in product quality and safety. Due to the negative impact of synthetic packaging materials on the environment, research organizations as well as the food industry are currently exploring the possibility of using biodegradable and renewable materials deriving from natural sources. Such biopolymers include: proteins (whey proteins, wheat, corn and soy proteins, gelatin), lipid derivatives (waxes, acetylated triglycerides) and carbohydrates (starch, cellulose and its derivatives, carrageenan, pectin, chitosan, alginates) used in food packaging applications. Alginates are natural hydrophilic polysaccharide biopolymers mainly extracted from marine brown algae. In the form of films or coatings, they exhibit: good film-forming properties, low permeability to O2 and vapors, flexibility, water solubility and gloss while being tasteless and odorless. When combined with additives such as organic acids, essential oils, plant extracts, bacteriocins and nanomaterials, they contribute to the retention of moisture, reduction in shrinkage, retardation of oxidation, inhibition of color and texture degradation, reduction in microbial load, enhancement of sensory acceptability and minimization of cooking losses. Alginates were initially used as a coating for perishable fresh fruits and vegetables to control respiration rate, but can be applied to a wide range of foods, such as meat, poultry, seafood and cheese products, resulting in the extension of product shelf life. When used as part of the principle of active, intelligent and green packaging technologies, alginates can work synergistically to yield a multi-function food packaging system comprising the ultimate goal of food packaging technology.